A numerical-experimental study on thermal evaluation of orthodontic tooth movement during initial phase of treatment. (February 2019) - Bonab, M. Fakhimi; Mojra, A.; Shirazi, M.
Abstract: The most desired target of orthodontic treatment is tooth movement as a result of application of efficient force system. In this study, effect of tooth loading is studied on temperature profile around the tooth at early stages of treatment. The basis of temperature variation is increase of cell number and activities in periodontium as a result of compression and tension of this layer. Highest cellular activities occur in the beginning of loading procedure and aim to reduce mechanical stress in the periodontium which finally ends up with orthodontic tooth movement during couple of years. To find out the correlation between temperature variation and the applied force, in vivo experiments are conducted on ten rats and temperature is measured in specific time periods. It is observed that temperature is higher in direction of the net force about 0.3 ℃ . Next, numerical finite element analysis is carried out on the rat tooth model. Mechanical stress results show that regions with compressive stress have rather high temperature in the experiments. Mechanical stress on periodontium-bone interface is multiplied by a coefficient to simulate cellular activities on this boundary as a heat source and thermal analysis is carried out to obtain temperature profile. The thermo-mechanical coefficient is identified for each rat by imposing the experimental temperatures on numerical outputs. For assessment of a treatment efficiency and deduction of the applied force, temperatures could be measured experimentally and compared with the corresponding numerical analysis temperature result obtained by employing the thermo-mechanical coefficient found earlier for each rat. Graphical abstract: fx1 Highlights: Effect of tooth loading is studied on temperature profile at early stage of treatment. Mechanical stress and temperature are correlated with thermo-mechanical coefficient. The coefficient is found out by in vivo experiments on rats after 2 weeks of treatment. Temperature profile can be obtained numerically by using this coefficient. Treatment evaluation is based on comparing experimental and numerical temperatures.